Three-dimensional ultrastructural analysis of human skin with the arrector pili muscle interacting with the hair follicle epithelium - Tomonobu Ezure; Kyoichi Matsuzaki; Hidetoshi Urakubo; Nobuhiko Ohno (Scientific Reports)
Abstract This study developed a three-dimensional ultrastructural analysis application using serial block-face scanning electron microscopy (SBF-SEM) to investigate surgically acquired human skin tissues containing the arrector pili muscle. We utilized the en bloc staining, including reduced osmium, thiocarbohydrazide, and lead aspartate, as well as the embedding using a carbon-based conductive resin. Next, we obtained serial images with SBF-SEM. The results revealed dense nerve fiber networks branching from nearby nerve fiber bundles outside the muscle and running among muscle fibers. Additionally, the dense nerve network running through and along arrector pili muscle fibers rarely penetrates the connective tissues between smooth muscle fibers and epithelial cells. Furthermore, in the observation area, no individual smooth muscle fibers formed adhesion structures with the epithelial cells of the hair follicle, ending in the dermal extracellular matrix near the epithelial cells. These results indicate the usefulness of this approach for three-dimensional ultrastructural analyses of human skin tissues comprising follicular units and revealing structural changes in skin tissues, especially the arrector pili muscle and nerve fibers with hair follicular epithelium, in aging and diseased conditions.